Three new blind species of the genus Nesamblyops Jeannel, 1937 (Anillini: Carabidae: Coleoptera) from New Zealand - Sokolov, Igor M. (Zootaxa, 2025)
Three new species of blind subterranean ground beetles of the tribe Anillini, genus Nesamblyops, are described from New Zealand: N. nunni sp. nov. (type locality: New Zealand, South Island, Central Otago, Old Man Range), N. larochellei sp. nov. (type locality: New Zealand, South Island, Lewis Pass), and N. pygmaeus sp. nov. (type locality: New Zealand, North Island, Tararua Range, Kāpiti Coastal District). All species are illustrated with digital images of habitus, body parts, and drawings of genitalia. Distribution maps for all species are also provided.